An in vivo assessment of Enterococcus hirae strain LAB3 as potential probiont for Asian seabass larvae (Lates calcarifer) against Vibrio harveyi infection - Masduki, Nur Fathiah; Zakaria, Muhamad Taufiq; Chong, Chou Min; Abd Karim, Murni Marlina (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
This study aimed to evaluate the ability of potential probiont Enterococcus hirae strain LAB3 in protecting Artemia nauplii and Asian seabass larvae against Vibrio harveyi infection. In the preliminary in vivo assay, strain LAB3 provided protective effect towards Artemia nauplii when challenged with V. harveyi. Pre-incubation of strain LAB3 at 106 CFUmL-1 with seabass larvae demonstrated highest protection after challenged (68%) compared to challenged group with no probiont added (17 %). Reduction of vibrios was observed in Artemia, seabass larvae and culture water at the end of the challenge assay. Thus, E. hirae strain LAB3 has potential application as probiotic in seabass larvae culture and also could be safely administered through its live feed, Artemia nauplii.